Affirmative Psychotherapy and Counseling for Lesbians and Gay Men. - Chernin, Dr. Jeffrey N. N. (SAGE Publications, 2002)
Affirmative Psychotherapy and Counseling for Lesbians and Gay Men offers a broad base of research, practice, and advocacy information about the special counseling needs of gays and lesbians. Authors Jeffrey N. Chernin and Melissa R. Johnson discuss universal themes as they apply to lesbian and gay clients, as well as issues unique to lesbians and gay men, including the treatment of same-sex couples and families, ethnic minority issues, and living with HIV/AIDS. They present sensible information on how to provide a safe therapeutic environment and how to interpret and apply psychological asses.